2003
DOI: 10.1007/s11661-003-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

The importance of viscoplastic strain rate in the formation of center cracks during the start-up phase of direct-chill cast aluminum extrusion ingots

Abstract: A comparison of experimental observations and computer simulations shows that trends in the occurrence and severity of center cracks in direct-chill (DC) cast ingots due to different initial casting speed histories may best be explained by the changes in viscoplastic strain rate close to the center of the base of the ingot. The thermomechanical histories of five ingots were simulated and correlations between stresses, strains, strain rates, and liquid pressure drops due to feeding restrictions were considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Influence of solidification behaviors It has been suggested that the generation and history of interdendritic strain can be related to some straining criteria such as strain rate and accumulated strain that are subjected to the material when it is still in mush zone. [35] To check the validity of these criteria, Fig. 3-Carbon concentrations during phase transformations, (a) mode 1, (b) mode 2, and (c) mode 3 of Fe-C alloys.…”
Section: Sensitivity Of Results and Discussionmentioning
confidence: 99%
“…Influence of solidification behaviors It has been suggested that the generation and history of interdendritic strain can be related to some straining criteria such as strain rate and accumulated strain that are subjected to the material when it is still in mush zone. [35] To check the validity of these criteria, Fig. 3-Carbon concentrations during phase transformations, (a) mode 1, (b) mode 2, and (c) mode 3 of Fe-C alloys.…”
Section: Sensitivity Of Results and Discussionmentioning
confidence: 99%
“…Prediction of hot tearing during DC casting is based on two steps, namely modeling of the thermomechanical behavior during solidification [2][3][4] and the implementing of hot-tearing criteria into this model. [5][6][7][8][9][10] The first step uses constitutive equations to describe the thermomechanical modeling, to calculate stresses and strains in the billet. Computed stresses or strains indicate the hot-tearing tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hot cracks are mostly formed in the start-up period of the DC casting process of extrusion ingots. [3] So, the start-up levels will also have an effect on the formation of cracks. However, few works reported the influence of start-up levels on cracks in DC casting process.…”
Section: Introductionmentioning
confidence: 99%
“…Several models about stresses, strains, and temperatures field during DC casting have been done generally by using a finite-element method. Hamdi et al [3] studied the casting process of AA6060 alloy using a finite element model ALSIM, and found the viscoplastic strain rate played an important role for the center cracks. Pokorny et al [4] used a viscoplastic stress model to simulate the stresses during the casting of binary magnesiumaluminum alloys, and the simulation results were reasonably good agreement with the measurements.…”
Section: Introductionmentioning
confidence: 99%